Consórcio microbiano isolado a partir do óleo derramado no nordeste brasileiro: biorremediação de áreas contaminadas - Castro, Luzia Gabrielle Zeferino de (2023)
August 2019, a mysterious oil spill affected coastal ecosystems in the Northeast of Brazil, considered the largest oil disaster in the last 30 years. The diversity of affected environments made it clear that there is no universal impact mitigation solution. However, one promising approach is the use of bioremediation technology by bioaugmentation. This study aimed to isolate, characterize, and evaluate cultivable microbiota associated with heavy oil, with the goal of selecting a customized consortium to accelerate the degradation of hydrocarbons. The bacterial isolation process used the enrichment technique on Bushnell Haas medium with + 3% m/v NaCl and 1% m/v from oiled samples collected on beaches in Ceará. The isolates were then identified from the analysis of the 16S rRNA gene sequences by Sanger sequencing. The biodegradation potential of oil fractions from each isolate was evaluated by the 2,6Dichlorophenolindophenol indicator method (DCPIP), using six hydrocarbon fractions as the sole carbon source. In addition, the prospection of biosurfactants was also evaluated through the kerosene emulsification index, surface tension reduction and oil dispersion. The biocompatibility between the isolates was evaluated using the antibiosis technique. After the evaluation process, 24 strains of bacteria were isolated and identified, from 14 different genera, belonging to the phyla Proteobacteria, Actinobacteria, and Bacteriodetes. Among these, the strains of Acinetobacter sp., Alcanivorax sp. and Martellella sp. stood out for their ability to degrade the largest number of hydrocarbons, emerging as the most promising to compose the consortium. Culture supernatants of Alcanivorax sp. FOR1501 and Acinetobacter sp. AMO1502 promoted kerosene emulsification, being candidates for the possible production of biosurfactants. The degradation assay with the consortia demonstrated that Acinetobacter sp. FLE1503 was the best strain for the degradation of alkanes (C4C25), while Alcanivorax sp. FOR1501 and Martelella sp. FOR1507 combined showed superior aromatic hydrocarbon degradation. Therefore, this study is the first record of microbial isolates associated with the oil spill, pointing to a customized consortium for alkanes and aromatic hydrocarbons as a promising approach to accelerate the cleaning of affected environments. The results of this study can be used to develop more effective and sustainable strategies for the management of oil spills in the future.